OPTIMALISASI PENGGUNAAN GROUND SUPPORT EQUIPMENT (GSE) DI EXISTING AREA TERHADAP TINGKAT KELANCARAN OPERASIONAL DI SISI UDARA BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Kusno Kusno; Mubarak Mubarak; Lady Silk Moonlight (Approach : Jurnal Teknologi Penerbangan, 2019)
Order control of equipment and vehicles operation on airside I Gusti Ngurah Rai International Airport Bali which is performed by AMC personnel is very important because the increasing number of flights accompanied by supporting equipment of aircraft ground service (GSE) also the one which serves the aircraft then it affects the increase in mobility on the airside. Then, it increase the potential for violation of order on airside. It is rightly for Apron Movement Control (AMC) personnel improve supervisory function in order to prevent violations that can endanger flight safety on the airside. There are still many violations that happened on the airside particularly on existing area caused by some factors, that is level of discipline which is still lacking from the operator themselves of the prevailing rules and regulations corresponding to Manual of Standard CASR – 139 Volume I Aerodrome and SKEP/100/XI/1985 along AMC personnel supervision that has not been maximized are several causes of violations that is happened on airside. Therefore, AMC personnel are expected to improve supervisory function so that violation rate can be minimized in order to ensure safety and security of mobility on airside.